ANALISIS DEFORESTASI KAWASAN HUTAN PADA KABUPATEN SIJUNJUNG - Hayati, Hafizah (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine 1). the forest area in Sijunjung Regency from 2000-2020, 2). the comparison of the consistency of the RTRW with forest areas in Sijunjung Regency. 3). factors affecting deforestation of forest areas in Sijunjung Regency. The research method used in this study is a mixed research method (mixed method). Based on the results of the study, the research results obtained 1). the change in forest area in 2000 was 208,982.63 ha, in 2010 it was 179,503.08 ha, in 2020 it was 153,070.05 ha. The forest area decreased from 2000-2010 by 29,479.55, from 2010-2020 by 26,433.03 ha, from 2000-2020 by 55,912.58 ha. 2). The consistency index value is 0.99 this happens because the system or regulations are not working properly. 3). Changes in forest areas in Sijunjung Regency are caused by several factors, including population growth, cultivation, land conversion, illegal logging, customary land, besides that natural disaster factors also affect such as floods and landslides.